Vestibular paroxysmia: Long-term clinical outcome after treatment - Chen, Chih-Chung; Lee, Ting-Yi; Lee, Hsun-Hua; Kuo, Yu-Hung; Bery, Anand K.; Chang, Tzu-Pu (Frontiers in Neurology, 2022)
Objective To study the long-term treatment outcome of vestibular paroxysmia (VP). Study design Retrospective study. Setting Tertiary referral hospital. Methods We analyzed records of 29 consecutive patients who were diagnosed with VP and who were treated with VP-specific anticonvulsants for at least 3 months. Patients were followed for a minimum of 6 months. We recorded and assessed starting and target dosage of medications, time to achieve adequate therapeutic response, adverse effects, and the rates of short-term and long-term remission without medication. Results All 29 patients were started on oxcarbazepine as first-line treatment, and 93.1% and 100% of patients reported good-to-excellent therapeutic response within 2 and 4 weeks, respectively. Three patients switched to other anticonvulsants at 3 months. At long-term follow-up (8–56 months), most (84.6%) oxcarbazepine-treated patients maintained good therapeutic response at doses between 300 and 600 mg/day. Eleven (37.9%) patients experienced complete remission without medication for more than 1 month, of which six (20.7%) had long-term remission off medication for more than 12 months. Nineteen (65.5%) patients had neurovascular compression (NVC) of vestibulocochlear nerve on MRI, but its presence or absence did not predict treatment response or remission. Conclusion Low-dose oxcarbazepine monotherapy for VP is effective over the long term and is generally well-tolerated. About 20% of patients with VP in our study had long-term remission off medication.